Development Of Electrical Motor Control Learning Media As Learning Support For Electrical Power Installation Courses In The Department Of Electrical Engineering - Supari Muslim; Tri Wrahatnolo; Sri Handayani; Erina Rahmadyanti; Nita Kusumawati; Joko Joko (Journal of Educational Science and Technology (EST), 2018)
Learning media is everything that can channel the message of learning resources in a planned manner, to create a conducive learning environment, where the recipient can carry out the learning process effectively and efficiently. Vocational learning must be effective in meeting basic objectives to prepare vocational graduates to be ready to work. Thus, it is an assignment for lecturers whose function is to prepare vocational teacher candidates. The question that arises is "how should a learning media be developed", so that the learning process in the classroom can run effectively and efficiently, so that students get optimum learning outcomes. For this reason, it is necessary to do research with the title "Development of Electrical Motor Control (EMC) Learning Media as Learning Support for Electrical Power Installation Courses in the Department of Electrical Engineering, Surabaya State University", with the aim of: (1) to develop Electrical Motor Control (EMC) Trainer through research and development (R & D); (2) to find out the feasibility level of the Trainer in a learning perspective; and (3) to determine the effectiveness of the EMC Trainer in the learning process. The study found that: (1) based on the validator's assessment, that the EMC Trainer that had been developed was very feasible to be used in learning in the Electrical Power Installation course; (2) based on the assessment of students, that the EMC Trainer is very suitable to be used in learning courses in Electric Power Installation; and (3) as many as 26 (74.28%) students get scores on learning outcomes in the 71-100 range, with good and excellent categories.